1998
DOI: 10.1021/jf9706033
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Two Novel Terpenoid Glucose Esters from Riesling Wine

Abstract: A glycosidic isolate of Riesling wine was separated with multilayer coil countercurrent chromatography (MLCCC). After acetylation and subsequent purification by high-performance liquid chromatography (HPLC), the glucose esters of (E)-2,6-dimethyl-6-hydroxyocta-2,7-dienoic acid (1) and (2E,6E)-10,11-dihydroxy-3,7,11-trimethyl-2,6-dodecadienoic acid (2) were identified for the first time as wine constituents. The identification was achieved by mass spectrometry (DCI-MS) as well as nuclear magnetic resonance spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 19 publications
(20 reference statements)
3
33
0
Order By: Relevance
“…Some non-odoriferous monoterpenes may undergo chemical transformations during wine storage and ageing, leading to the appearance of interesting odoriferous monoterpenes. For example, wine lactone may be formed from E-2,6-dimethyl-6-hydroxy-2,7-octadienoic acid (Bonnländer et al, 1998) and the possible precursors of rose oxide could be 3,7-dimethylocta-5-en-1,7-diol and 3,7-dimethylocta-7-en-1,6-diol (Rapp et al, 1984). On the other hand, monoterpenic polyols (e.g.…”
Section: Varietal Compoundsmentioning
confidence: 99%
“…Some non-odoriferous monoterpenes may undergo chemical transformations during wine storage and ageing, leading to the appearance of interesting odoriferous monoterpenes. For example, wine lactone may be formed from E-2,6-dimethyl-6-hydroxy-2,7-octadienoic acid (Bonnländer et al, 1998) and the possible precursors of rose oxide could be 3,7-dimethylocta-5-en-1,7-diol and 3,7-dimethylocta-7-en-1,6-diol (Rapp et al, 1984). On the other hand, monoterpenic polyols (e.g.…”
Section: Varietal Compoundsmentioning
confidence: 99%
“…Indeed, Pagot et al (27) showed that peroxisomal ␤-oxidation of ricinoleic acid leads to ␥-decalactone, a peachy aroma compound. Two other elemental formulas could be related to terpenoid glucose esters at m/z 325.2024 and 345.1556 (28). The latter is a glucose ester of (E)-2,6-dimethyl-6-hydroxyocta-2,7-dienoic acid and was previously detected in Riesling wine (29 (30).…”
Section: Rising and Collapsing Bubbles Act As A Continuous Paternostementioning
confidence: 84%
“…Typically in these studies, the glycoconjugates are initially isolated and fractionated from the matrix using low-(or atmospheric) pressure liquid chromatography, HPLC, counter-current chromatography (CCC), and/or supercritical fluid extraction (SFE) (Strauss et al 1987, Winterhalter et al 1990, Bonnländer et al 1998, Palma et al 2000. The isolated glycoconjugate fraction is then analyzed directly by fast atom bombardment tandem MS (FAB-MS) (Marinos et al 1994), HPLC-MS and/or MS/MS (Hayasaka et al 2010a), and matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) MS (Nasi et al 2008).…”
Section: Analysis Of Glycoconjugatesmentioning
confidence: 99%